A high-performance asymmetric supercapacitor based on a directly grown nickel bicarbonate/nickel foam composite. (20th October 2015) - Long, Lu; Fu, Weidong; Yan, Minglei; Yao, Yadong; Wang, Hongjing; Wang, Meng; Liao, Xiaoming; Yin, Guangfu; Huang, Zhongbing
Graphical abstract: Highlights: Ni(HCO3 )2 /NF has a high specific capacitance of 2128.57 F g −1 at 2.5 mA cm −2 . An asymmetric supercapacitor based on Ni(HCO3 )2 /NF and Fex Cy /C is assembled. The asymmetric supercapacitor exhibits high energy density and power density. The asymmetric supercapacitor shows good cycling stability. Two devices connected in series can light five LED indicators or a LED for 30 min. Abstract: Three-dimensional (3D) network structure nickel bicarbonate/nickel foam (Ni(HCO3 )2 /NF) composite was synthesized by a simple one-pot hydrothermal process. The electrochemical properties of the as-prepared samples were investigated through the cyclic voltammetry and galvanostatic charge/discharge measurements. The results show that the specific capacitance of Ni(HCO3 )2 /NF reaches up to 2128.57 F g −1 (corresponding to a specific area capacitance of 7.45 F cm −2 ) at a current density of 2.5 mA cm −2, and the capacitance is still 876.19 F g −1 (3.07 F cm −2 ) even at 50 mA cm −2 . Considering the excellent electrochemical performances of Ni(HCO3 )2 /NF electrode, an asymmetric supercapacitor based on Ni(HCO3 )2 /NF anode and Fex Cy /C cathode was assembled, which exhibited high energy density and power density. The maximum energy density of the asymmetric supercapacitor is up to 24.96 Wh kg −1 at a power density of 87.75 W kg −1, besides, the power density can reach 1754.37 W kg −1 at 6.92 Wh kg −1 . Moreover, two such 1 cm 2 devices connected in series could light five LED indicators (40 mW) after charging only 50 s, and power a LED indicator with the same power for half an hour after charging to 3.2 V. The results demonstrate that our asymmetric supercapacitor is a promising device for practical applications.